ПРОФЕССИОНАЛ ТАЪЛИМ МУАССАСАЛАРИ УЧУН МУЛЬТИМЕДИАЛИ ЭЛЕКТРОН АХБОРОТ ТАЪЛИМ РЕСУРСЛАРИ ЯРАТИШГА ҚЎЙИЛАДИГАН ТАЛАБЛАР - Кунназаров, И.С. (SCIENCE and SOCIETY, 2020)
The article deals with the problems of creating multimedia electronic information educational resources for professional educational institutions.